A Strategy for Peace- Asia - Ungku Abdul Aziz, Ungku Abdul Hamid
Monopolistic and monopsonistic, (or the MM system) are always the core problems in the developing rural areas in Southeast Asia. This system is closely interlocked with systems of employment, tenancy and also the exploitation of the credit system. The social relationship and the ethnicity patterns have sustained the system over a period of time. Discrimination of education, health facilities and public welfare have worsened the problem even since the colonialization period. Why is the peasant unable to escape from the exploitative system? What are the main obstacles to breaking the ethnicity clan-dialect operating system? What are the myths that politicians held on the peasants from the rural area? Are there steps taken by the Government or politicians to assist the peasants in increasing the production? What are the steps taken by the MM operators to secure their MM status? How did the MM operator evolve after the war ended? Education, health facilities and public welfare play an important role in improving the living standard of the nations. However, what are the reasons behind that the kids from the rural area are unable to gain access to the tertiary education? What are the differences between the health facilities and public welfare provided in the urban and rural area? The surge of mass media allows the peasant to have a better view of current social and economic conditions. Politicians tried to sharpen the dissatisfactory feeling by spreading distorted views. In the end, all these erupted into vicious violence which shaken the stability and peace of the society.